Stagnant Textualism and Epistemological Crisis: Revisiting Hadith Scholarship in Indonesia’s Islamic Universities - Rifqi Muhammad Fatkhi; Hilmy Firdausy (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2026)
This study explores the epistemological orientation of hadith studies in Indonesia following a decade of institutional expansion across five major State Islamic Universities. Based on 1,272 undergraduate theses (2018–2025) and official curricula, the research employs qualitative content analysis to examine five dimensions—object of study, sources, problem orientation, methodology, and epistemic direction—interpreted through al-Jābirī’s tripartite framework (bayānī, ʿirfānī, and burhānī). The findings indicate a structural dominance of bayānī textualism, with matn-focused research comprising 53%, living hadith accounting for 21%, and isnād studies remaining marginal. Classical methods prevail at approximately 60%, while modern and hybrid approaches appear inconsistently, and curricular structures reinforce this conservatism by allocating up to 93% of instructional hours to riwāyah-oriented courses. Although UIN Yogyakarta and Jakarta exhibit partial integration of rational-critical approaches, most institutions maintain normative and thematic orientations. The study concludes that institutional growth has resulted in selective adaptation rather than paradigmatic transformation and recommends embedding rational-critical reasoning, interdisciplinary methods, and socially grounded research within core curricula to enable a shift from textual reproduction toward context-sensitive interpretation.